Structural determinants of life strategies: Actualization of collectivist and individualistic values - Grishchenko, Mikhail Aleksandrovich; Serikov, Anton Vladimirovich; Skudnova, Tatyana Dmitrievna (Opción, 2019)
The article deals with the idea that the life strategies of Russians involve the determinants and self-determinants of the choice of life goals, priorities and ways of its implementation via the study of collectivist and individualistic values is conceptualized at the level of structural, functional, institutional, social and cultural, and subject-activity approaches. As a result, the symbolism of collectivist values and instrumental values of individualistic values are important for Russian rich people. The authors conclude that the existing social inequalities affect the actualization of value self-determinants in correlation with the traditional understanding of values as an ideal model.